Career Maturity in Relation to Differences in School Curriculum - Khan, Sar B.; Alvi, Sabir A. (Canadian Journal of Counselling and Psychotherapy, 2011)
Two studies were undertaken to examine differences in career maturity among four curriculum groups: academic business, technical, and general. In Study I, Crites' Career Maturity Inventory was administered to students in grades nine through twelve. In Study II, a specially developed measure of career development was administered to students in grade 12. Results of both studies indicated that the academic group scored higher than the other three groups.